Artistic institution and post-truth. An effective relationship - Harillo Pla, Adriá (2018)
The present article pretends to establish a connection between the concepts of artistic institution and its most frequent expression "artworld" with that of post-truth. This last term, approved recently by the Royal Academy of Language, is what allows us to bring an innovative vision to this relationship. As a hypothesis, we will defend that both concepts have a clear link and that, the nature of this, it is based on a principle of effectiveness.